Prevalence of and Risk Factors for Genito-Pelvic Pain/Penetration Disorder: A Population-Based Study of Iranian Women. Issue 7 (30th May 2019) - Alizadeh, Ameneh; Farnam, Farnaz; Raisi, Firoozeh; Parsaeian, Mahboubeh
Abstract: Introduction: To date, few studies have investigated the prevalence of sexual pain in the context of the new diagnostic concept of genito-pelvic pain/penetration disorder (GPPPD). Aim: To evaluate the prevalence of GPPPD and its associated factors. Methods: This was a population-based, cross-sectional study of 590 healthy married women age 18–70 years conducted between May and October 2017 in Tehran, Iran. Main Outcome Measures: Research tools included demographic characteristics checklist, factors affecting GPPPD, sexual distress and self-reporting of pain during intercourse, 2 standard questionnaires on depression (Patient Health Questionnaire 9) and Binik's guideline for the diagnosis of GPPPD. Results: 196 women (33%) reported pain or fear in answer to self-report questions. Administration of Binik's guideline yielded a GPPPD prevalence of 16% (n = 94 women); however, this number decreased to 62 women (10.5%) when sexual distress was taken into account; thus, the final prevalence of GPPPD was considered to be 10.5%. However, if the threshold in Binik's guideline was lowered to also include those reporting "somewhat" pain in addition to the group reporting "moderate" and "quite a bit or always, " then the prevalence of GPPPD increased to 25.8%. The results of backward logistic regression identified a strong aversion to looking at or touching the genitalia (odd ratio [OR] = 4.3), low sexual satisfaction (OR = 3.1), and severe depression (OR = 6.6) as independent risk factors for a diagnosis of GPPPD and secure financial status (OR = 0.3) and a high level of marital satisfaction (OR = 0.2) as protective factors against a diagnosis of GPPPD. Clinical Implications: Reliable diagnosis of GPPPD is crucial. Application of validated tools may mitigate the overestimation of GPPPD prevalence. Simultaneously, clinicians' judgment is essential in assessing a reasonable threshold and preventing underestimation that leads to the exclusion of women suffering from pain. Strengths & Limitations: The present study is one of the few evaluating the prevalence of GPPPD according to the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) definition and Binik's guideline. The study also aims to point out some new perspectives on merging the 2 concepts of vaginismus and dyspareunia. Study limitations include the evaluation of factors affecting GPPPD based on self-reporting and possible recall bias. Conclusion: Further research is needed to determine the appropriate threshold for a diagnosis of GPPPD. We suggest that a woman with mild to moderate pain or fear of vaginal penetration is under sexual distress and cannot be neglected. In addition, problems may arise following the DSM-5 merging of the 2 disorders of vaginismus and dyspareunia, owing to the significant prevalence and distress of lifelong vaginismus in some cultures.